Blast-induced dynamic responses of reinforced concrete structures under progressive collapse. Issue 16 (22nd August 2022) - Pham, Anh Tuan; Brenneis, Christian; Roller, Christoph; Tan, Kang Hai
Abstract : To study the response of reinforced concrete structures under progressive collapse induced by an actual blast event, an experimental programme on reinforced concrete frames subjected to contact detonation was conducted. The tested structure included a double-span beam with a middle joint, side columns and beam extensions connected to external restraints. The experimental programme employed similar geometry, reinforcing arrangement, material properties and boundary restraints from previous quasi-static as well as free-fall dynamic test series, which focused on the effects of horizontal restraint conditions on the mobilisation of catenary action. Compared to the corresponding static and free-fall tests conducted previously, the blast-induced tests simulated the condition of a progressive collapse event triggered by an explosive charge which is close to actual accidental/terrorist situations. As a result, initial effects/damages created by the initial blast effects – that is uplift of the double-span beam and blast pressure on beam and column – were witnessed and well captured. Damage patterns and failure modes from the blast tests were compared with those from related quasi-static and free-fall tests to emphasise the actual behaviour of structures under realistic explosive attacks. Finally, the blast tests also indicated the limitations of some simplified dynamic assessment methods when applying the single column removal assumption.